Prostate carcinoma - Cieśliński, Piotr; Dadej, Roland; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
The carcinoma of the prostate is a neoplastic disease, which is more and more frequently detected in men. Prostate carcinoma generally occurs in men beyond middle age. It constitutes the third death cause among neoplastic diseases (5%) in Poland. The most important risk factors are: advanced age of the patients, familial prevalence of the disease, black race and high-fat diet. Prostate cancer usually develops in the outer part of the prostate gland (75%), causing a change in the texture of the gland. The most important steps in diagnosing the prostate cancer are: digital rectal examination (DRE), evaluation of the prostate-specific antigen (PSA) level in the blood, transrectal ultrasonography (TRUS) and ultrasound-guided biopsy. The most important prognostic factors are: degree of the cancer progression (staging), degree of histological differentiation (grading), and the serum level of the PSA. Determination of the prognostic factors makes possible to evaluate the condition of the patient and to establish a proper therapy. The patients with diagnosis of prostate cancer, confirmed by the result of the transrectal biopsy, in clinical stage not higher than T2 are qualified to the radical treatment. This kind of treatment can be performed only in patients with organ confined disease and when the patients can benefit from it, that means in men whose expected survival is not shorter than 10 years. Radical treatment comprises a complete removal of the prostate (radical prostatectomy) or radiotherapy (brachytherapy, external-beam radiotherapy). In case of an advanced disease, only palliative procedures can be carried (usually hormonal therapy - androgen deprivation). The most adequate method for the completely informed patient should be chosen in each case of planed treatment. Taking into consideration a rapid growth in occurrence of the prostate cancer, an early detection of the disease, a proper qualification and adequate therapy is of the great importance.